Effect of added lipases of psychrotrophic Yersinia, Enterobacter and Citrobacter spp. on the keeping quality of milk and fat rich milk products - SWARNA, C; PRABHA, R; SHANKAR, P A (The Indian Journal of Animal Sciences, 2013)
Cell-free filtrates of psychrotrophic Yersinia sp. M18, Enterobacter sp. M31 and Citrobacter sp. M33 containing lipase activities were precipitated with ammonium sulphate and the precipitates after dialysis were introduced separately into aseptically drawn milk, pasteurized cream, butter and Mee, and stored at 7Â°C. A6-fold increase in FFA content in refrigerated milk containing added Yersinia lipase, and rancidity were observed from 10th day of storage. In refrigerated milks containing Enterobacter and Citrobacter lipases there wos no appreciable increase in FF A content nor the samples exhibited rancidity even after 18 days of storage. Addition of Yersinia lipase to cream resulted in 2-fold increase in oleic acid content and showed rancidity after 14 days of storage at 7Â°C. While addition of Jipases of Enterobacter and Citrobacter through increased the oleic acid content but did not show rancidity even at the end of 16 days storage period. In butter. Enterobacter lipase produced highest oleic acid content followed by lipases of Citrobacter and Yersinia. But none of the ghee samples containing Yersinia. Enterobacter and Citrobacter lipases exhibited ranr idity during storage period nor caused an appreciable increase in oleic acid content.